Risk factors for secondary vertebral compression fracture after percutaneous vertebral augmentation: a single-centre retrospective study - Jin Tang; Siyu Wang; Jianing Wang; Xiaokun Wang; Tao Li; Lulu Cheng; Jinfeng Hu; Wei Xie (Journal of Orthopaedic Surgery and Research)
Abstract Objective To determine the incidence of secondary vertebral compression fracture (SVCF) after percutaneous vertebral augmentation (PVA) and its correlative risk factors, and to provide theoretical evidence for clinical practice. Methods A retrospective analysis of 288 cases of PVA completed in our hospital from June 2020 to June 2023 was performed, and the patients were divided into the non-secondary vertebral compression fracture group (N-SVCF group) and the secondary vertebral compression fracture group (SVCF group) according to whether SVCF occurred during the postoperative follow-up review. Gender, age, body mass index (BMI), T value of bone mineral density (BMD-T), underlying diseases (hypertension, diabetes mellitus, coronary heart disease, chronic obstructive pulmonary disease), intravertebral vacuum cleft (IVC), amount of bone cement injected, classification of cement diffusion, anterior vertebral recovery ratio, local Cobb angle correction rate, leakage of bone cement into the intervertebral space, and fat infiltration rate (FIR) of paraspinal muscles were collected from the patients. The incidence and risk factors of SVCF after PVA were evaluated using univariate and multivariate logistic regression analysis, and the predictive value of the independent risk factors was evaluated using receiver operating characteristic curve (ROC) to determine the cut-off points at which they were meaningful for the development of SVCF. Results In our study, the incidence of SVCF was 14.60% (42/288) in 288 patients who underwent PVA. Univariate analysis showed that age, BMI, fat infiltration rate of paraspinal muscles, cement leakage into the intervertebral space, unilateral/bilateral pedicle puncture approach and presence of IVC were statistically different between N-SVCF and SVCF (P < 0.05). Multifactorial regression analysis and ROC regression analysis revealed that the fat infiltration rate of the psoas major and erector spinae muscles, cement leakage into the intervertebral space, and IVC (P < 0.05) were risk factors for the incident of SVCF after PVA (P < 0.05). Psoas major (FIR) more than 5.490% and erector spinae (FIR) more than 52.413% had a high possibility of the occurrence of SVCF after PVA. Conclusion In this study, logistic regression combined with ROC curve analysis indicated that FIR of psoas major and erector spinae, cement leakage in the intervertebral space, and IVC were risk factors for the occurrence of SVCF after PVA. Psoas major (FIR) more than 5.490% and erector spinae (FIR) more than 52.413% had a high possibility of the occurrence of SVCF after PVA.